2021
DOI: 10.1002/mc.23365
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoid ursolic acid drives metabolic rewiring and epigenetic reprogramming in treatment/prevention of human prostate cancer

Abstract: Ursolic acid (UA) is a triterpenoid phytochemical with a strong anticancer effect. The metabolic rewiring, epigenetic reprogramming, and chemopreventive effect of UA in prostate cancer (PCa) remain unknown. Herein, we investigated the efficacy of UA in PCa xenograft, and its biological effects on cellular metabolism, DNA methylation, and transcriptomic using multi-omics approaches. The metabolomics was quantified by liquid-chromatography-mass spectrometry (LC-MS) while epigenomic CpG methylation in parallel wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…DNA Methyl‐seq profiled DMRs were used to show the epigenomic modulations by NaB in HCT116 cells as we have reported previously in other systems. [ 38,48 ] More than 50% DMRs were detected in the promoters and distal intergenic regions ( Figure 2 a). The methylation differences >10% of specific genes were applied for the cutoff of DMRs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA Methyl‐seq profiled DMRs were used to show the epigenomic modulations by NaB in HCT116 cells as we have reported previously in other systems. [ 38,48 ] More than 50% DMRs were detected in the promoters and distal intergenic regions ( Figure 2 a). The methylation differences >10% of specific genes were applied for the cutoff of DMRs.…”
Section: Resultsmentioning
confidence: 99%
“…LC-MS metabolomic analysis was performed in Metabolomics Shared Resources, Rutgers Cancer Institute of New Jersey (CINJ) as previously reported. [47,48] 3 ×10 6 HCT116 cells were seeded in 10-cm cell culture dishes (n = 3) and cultured in dialyzed FBS DMEM medium overnight. For the stable isotope labeling of methyl group, methionine free DMEM media would be used, and supplemented with 2 mM 13 C-methionine as this study had performed with other isotopes previously.…”
Section: Lc-ms Metabolomic Analysismentioning
confidence: 99%
“…We found that SFN treatment and UVB irradiation for 6 h increased the proportion of SAM and SAM/SAH in normal HaCaT cells. Our previous research showed that ursolic acid drives metabolic rewiring including SAM potentially driving epigenetic CpG methylation reprograming and transcriptomic signaling, resulting in the overall anticancer chemopreventive effect . Isothiocyanates, particularly SFN, have been studied in vivo, in vitro, as well as in humans. ,, Our data demonstrated that SFN induced metabolic changes in both normal and 10wk-UVB HaCaT cells, such as CDP-choline, glutathione disulfide, and UDP-glucuronate.…”
Section: Discussionmentioning
confidence: 66%
“…It has been reported that miRNAs target proliferation-related genes and proteins, such as PKM, Akt, and MEF2D, to regulate tumor cell proliferation ( Xu et al, 2020 ). Tan IIA suppresses the proliferation of AML cells (HL-60 and THP-1), glioma cells, esophageal cancer cells (EC109), breast cancer cells, and NSCLC cells through targeting miR-497-5p/Akt3, miR-122/PKM2, miR-16-5p/TLN1, miR-125b/STAR13, and let-7a-5p/aurora kinase A (AURKA), respectively ( Zhang et al, 2016 ; Liu et al, 2020a ; Liu et al, 2020 ; Nie et al, 2020 ; You et al, 2020 ; Li et al, 2022 ). Moreover, tan I, CPT, and tan IIA share common targets, including miR-137 and let-7a-5p, which function in inhibiting the proliferation of NSCLC by regulating the expression of ULK2/IBTK and AURKA, respectively; these common targets may be a result of highly similar chemical structures ( Zhang et al, 2016 ; Liu et al, 2020a ).…”
Section: Targeting Micrornas (Mirnas)mentioning
confidence: 99%
“…Abnormal increased DNA methylation leads to transcriptional repression and decreased gene expression ( Pan et al, 2018 ). Studies have reported that S. miltiorrhiza bioactive compounds regulate the level of methylation in tumor cells and inhibit tumor development ( Kim et al, 2016 ; Li et al, 2022 ). For example, tan IIA, LUT, and UA target the abnormal hypermethylation at the CpG methylation region in the Nrf2 promoter by reducing the expression of DNA methyltransferases (DNMTs), including DNMT1, DNMT3a, and DNMT3b, thereby inhibiting cell proliferation of skin and colon cancers ( Wang et al, 2014 ; Kim et al, 2016 ; Zuo et al, 2018 ).…”
Section: Regulation Of Epigenetic Enzymesmentioning
confidence: 99%